MASS-FORMING CHRONIC PANCREATITIS: A CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Background: Mass-forming pancreatitis is a distinct clinical entity in which inflammation is localized, creating a focal mass. Differentiating mass-forming pancreatitis from pancreatic cancer remains one of the most significant challenges for radiologists. Due to its tumor-like presentation, patients are frequently misdiagnosed with malignancy.Case report: We present a case of a 70-year-old female with a history of breast cancer who was admitted with obstructive jaundice. Ultrasound, CT scanner and magnetic resonance imaging revealed a mass in the pancreatic head associated with enlargement of the pancreatic body and tail. Laboratory findings showed elevated bilirubin; however, tumor markers (CEA, CA 19-9) and pancreatic enzymes (amylase, lipase) were within normal limits. Notably, initial blood work showed leukocytosis with an increased neutrophil percentage. Following biliary drainage to relieve the obstruction, subsequent tests revealed a persistent elevation in both the absolute white blood cell count and the eosinophil count (percentage and absolute), along with markedly high serum IgE and a borderline increase in IgG4 levels. Based on these findings, the patient was diagnosed with a suspected case of Type 1 autoimmune pancreatitis, characterized by concurrent peripheral eosinophilia and elevated serum IgE levels, which showed a favorable response to Corticosteroid therapy.Conclusion: Type 1 autoimmune pancreatitis with eosinophilia and hyper-IgE can manifest as a mass-forming pancreatic lesion, mimicking pancreatic malignancy. Recognizing this specific clinical phenotype is crucial in clinical practice to ensure an accurate diagnosis and prevent unnecessary surgical interventions.
Keywords: Autoimmune pancreatitis, eosinophilia, pancreatic cancer, mass-forming pancreatitis, IgE.